Hepatitis C virus and hepatocellular carcinoma: carcinogenesis in the era of direct-acting antivirals - Fiehn, Felix; Beisel, Claudia; Binder, Marco (Current opinion in virology, 2024)
Chronic hepatitis C virus (HCV) infection is a major cause of hepatic fibrosis and cirrhosis, with a risk for the development of hepatocellular carcinoma (HCC). Although highly effective direct-acting antivirals (DAAs) are available, the incidence, morbidity, and mortality of HCV-associated HCC are still high. This article reviews the current knowledge of the mechanisms of HCV-induced carcinogenesis with a special focus on those processes that continue after virus clearance and outlines implications for patient surveillance after DAA treatment.